Links between socioeconomic disadvantage, neural function, and working memory in early childhood. Issue 6 (22nd August 2021) - Li, Xinge; Lipschutz, Rebecca; Hernandez, Samuel Montero; Biekman, Brian; Shen, Shutian; Montgomery, Diana A.; Perlman, Susan B.; Pollonini, Luca; Bick, Johanna
Abstract: Children reared in socioeconomically disadvantaged environments are at risk for academic, cognitive, and behavioral problems. Mounting evidence suggests that childhood adversities, encountered at disproportionate rates in contexts of socioeconomic risk, shape the developing brain in ways that explain disparities. Circuitries that subserve neurocognitive functions related to memory, attention, and cognitive control are especially affected. However, most work showing altered neural function has focused on middle childhood and adolescence. Understanding alterations in brain development during foundational points in early childhood is a key next step. To address this gap, we examined functional near‐infrared‐spectroscopy‐based neural activation during a working memory (WM) task in young children aged 4–7 years ( N = 30) who varied in socioeconomic risk exposure. Children who experienced greater disadvantage (lower income to needs ratio and lower Hollingshead index) exhibited lower activation in the lateral prefrontal cortex than children who experienced less to no disadvantage. Variability in prefrontal cortex activation, but not behavioral performance on the WM task, was associated with worse executive functioning in children as reported by parents. These findings add to existing evidence that exposure to early adversity, such as socioeconomic risk, may lead to foundational changes in the developing brain, which increases risk for disparities in functioning across multiple cognitive and social domains.